2001
DOI: 10.1023/a:1009412130417
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Among CMA3, aniline blue, SDS test, and acridine orange, CMA3 was the most sensitive and specific test that can be used along with routine semen analysis for more precise prediction of fertilization rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(20 citation statements)
references
References 39 publications
2
17
1
Order By: Relevance
“…These results were in agreement with the study of Esterhuizen et al [57] who showed that fertilization rate in ICSI is lower when semen samples with high rates of nuclear condensation are used. Other studies reported that sperm with high rates of blue-stained nucleus can affect fertilization rate following in vitro fertilization procedure and pregnancy rates [58, 59]. Also, the risk of spontaneous abortion would be significantly higher after artificial insemination using ejaculates with high rates of immature nuclear sperm [60, 61].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results were in agreement with the study of Esterhuizen et al [57] who showed that fertilization rate in ICSI is lower when semen samples with high rates of nuclear condensation are used. Other studies reported that sperm with high rates of blue-stained nucleus can affect fertilization rate following in vitro fertilization procedure and pregnancy rates [58, 59]. Also, the risk of spontaneous abortion would be significantly higher after artificial insemination using ejaculates with high rates of immature nuclear sperm [60, 61].…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike aniline blue staining, they found a significant difference in the percentage of CMA3-positive sperm between the two groups. This difference between AB and CMA3 staining could be due to the fact that CMA3 staining is a more sensitive and specific test and CMA3 reveals not only the presence of excessive histones but also protamine deficiency [59]. Similarly, Razavi et al [49] did not find any correlation between excessive histones evaluated by AB staining and fertilization rate following ICSI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Any changes in process of substitution of protamine directly effects on fertilization rate and embryo quality and pregnancy outcome. [36]…”
Section: Discussionmentioning
confidence: 99%
“…Histone-rich nuclei of immature sperm are rich in lysine and will consequently take up the blue stain. On the other hand, protamine rich nuclei of mature sperm are rich in arginine and cysteine and contain relatively low levels of lysine, which means they will not be stained by Ab (25). A drop of semen was spread on the glass slides and allowed to air-dry.…”
Section: Methodsmentioning
confidence: 99%